Cobac Control Measures On The Performance Of Mfis - Felix, Dr. Nkiendem; Roland N., Gahmuti; Ayenika, Felix Nyuysemo; Sylvie, Fokeng; Asah, Nchitu Polycarpe (International Journal of Scientific Research and Management (IJSRM), 2018)
Globally, the emergence of MFIS presents an unprecedented opportunity to extend financial services to the vast majority of the population. In Cameroon, MFIs and banks are governed by a series of enactments (conventions, laws, ordinance, presidential decrees, ministerial orders and circulars). Cobac control measures are becoming increasingly important to the performance of microfinance institutions in Cameroon. This measures seems to be indispensible for customer satisfaction as a measure of performance. We therefore set out to verify the level to which these measures influence the performance of microfinancial institutions. Data was collected from 160 respondents in the northwest and littoral regions in Cameroon. Measures of dispersion were studied including inferential statistics in terms of person correlation, test of hypothesis, analysis of variance, chi square. Our results show that COBAC control measures positively influence the performance of MFIs. Thus MFIs should re-enforce the implementation of COBAC control measures instead of considering them as threats